Projecting Faith: French and Belgian Catholics and the Magic Lantern Before the First World War - Kessler, Frank (Material religion, 2020)
Around 1900, the Catholic Church in Belgium and France started to systematically use the magic lantern for religious education, but also as a propaganda tool in their fight against their laic opponents in both countries. In the course of the nineteenth century, the magic lantern had become a major visual mass medium in Europe and the United States. The light beam of the lantern was seen as a powerful means to sustain faith and disseminate the views of the Church. While numerous members of the Catholic clergy embraced the projections lumineuses as a continuation of the long-standing tradition to teach the gospel through images, from glass windows to paintings, they had to face opposition by those who thought the magic lantern unfit to be used to lecture on religious matters. Despite such resistance, the projected image became an important medium used throughout the first decades of the twentieth century by the Catholic Church.